Matter-wave interference of a native polypeptide - A. Shayeghi (Nature Portfolio, 2020)
Matter-wave interferometry of complex molecules is challenging due to difficulties in preparing and detecting molecular beams. Here the authors demonstrate quantum behavior of a polypeptide using matter-wave interference in an all-optical time-domain Talbot-Lau interferometer.